LOAN AND CALQUE FOUND IN TRANSLATION OF ENGLISH INTO INDONESIAN - Arif Topan, Tegar; Permatasari, Idha Dwi; Arsiwela, Arsiwela (Journal of Language and Literature, 2024)
This paper is to investigate loanwords and calques in the English to Indonesian translation of the book The First Four Years as well as to pinpoint the most often utilized translating technique. The researchers particularly looked at whether the forms used were calques or word or phrasal borrowing. Laura Ingalls Wilder's book as well as its Indonesian adaptation by Djokolelono provided the materials. Descriptive qualitative and quantitative approaches were used in concert. While the quantitative technique computed the percentages of several non-linguistic elements, the qualitative approach was utilized to explain the findings in context. The results revealed that in the first chapter, 22 instances were identified as loans and 33 as calques, with the majority being in word form. The predominant strategy for translating from English to Indonesian was found to be calque.